Quantification of secondary phases in 6063 aluminium alloy - Tan, Sin Hooi (2021)
The evaluation on AA6063 alloy’s homogeneity by quantify secondary phases using appropriate techniques, investigate on the morphology and chemical composition of secondary phases present in AA6063 alloy, and the correlation between alloy’s mechanical and microstructural properties are been conducted. Two types of secondary phases namely,